Carbon footprint in the value chain of Paria cheese from the Lake Titicaca basin area - Condori Cusi, Rubén (2023)
The objective of this study was to calculate and analyze the carbon footprint (CF) in the context of the value chain of Paria cheese produced in four plants in the Lake Titicaca basin area in Peru. To determine the value added (VA), the market price was considered as the gross value of production (GVP), composed of VA and intermediate consumption (IC). The VA was disaggregated into labor, capital, land, and taxes; and the IC into domestic (D) and imported (I). The CF was calculated using the Intergovernmental Panel on Climate Change (IPCC) Level one methodology, complemented with a product life cycle analysis (PLCA). The VA, per kilogram of final cheese product, at April 2020 prices, was determined to be 10.68 soles in Acora, 9.30 in Plateria, 11.51 in Huata, and 10.31 in Taraco; mainly constrained by the market price. Regarding CF, it was determined to be 10.54 kg of CO2eq per kilogram of cheese product in Acora, 10.98 in Plateria, 9.98 in Huata, and 9.41 in Taraco; with the majority of CF emissions occurring in the livestock phase. It was also determined that CF varies among plants, with the highest CF in livestock attributed to CH4 emissions from enteric fermentation, and in agriculture to N2O. Finally, the VA was linked to CF through an environmental profitability indicator, highlighting the Huata plant with 1.15 soles per kilogram of CO2eq of cheese product.